PENGARUH MOTIVASI KERJA, KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA PENGELOLAAN TAMAN BACA MASYARAKAT (TBM) DI KOTA TANGERANG SELATAN - Listiani; Yulita Pujilestari; Estiningsih Trihandayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the influence of motivation, competence, and work discipline partially and simultaneously on the performance of the management of Community Reading Parks (TBM) in South Tangerang City. The research approach used is quantitative with an associative approach. The population in this study were all managers of Community Reading Parks (TBM) in South Tangerang City with a sample of 144 respondents. The data collection technique was carried out through a questionnaire with a Likert scale instrument that has been tested for validity and reliability. Data analysis includes classical assumption tests and multiple linear regression analysis using SPSS software version 27. The results of the study indicate that partially, there is a positive and significant influence of work motivation on management performance with a very strong correlation value of 0.933 and a t-count value of 30.873. Competence is also proven to have a positive and significant influence on management performance with a strong correlation coefficient of 0.899 and a t-count value of 24.409. Likewise, work discipline has a positive and significant influence on management performance with a strong correlation value of 0.894 and a t-count value of 23.837. Simultaneously, these variables contribute a very strong influence on management performance through a multiple regression equation model Y = 10.306 + 0.496X1 - 0.195X2 + 0.258X3. Testing the coefficient of determination (r2) shows that the contribution of motivation, competence, and work discipline together is 93.6% on TBM management performance, while the remaining 6.4% is influenced by other factors outside the research variables. This indicates that effective improvements in TBM management performance can be achieved through strengthening work motivation, developing literacy competencies, and enforcing work discipline among managers on an ongoing basis.